E –payment applied on hebron municipality - qadi, Nour eden; abu eisheh, fadil; haniny, wisam (جامعة بوليتكنك فلسطين - تكنولوجيا المعلومات, 2006)
The main goal of the project is to build web-based system Hebron Municipality. This project offers Internet-based paying system facility through which the consumer can view and pay his bills via Hebron Municipality web site. In addition, he can view his consumption report. To enable consumer to use this eServices, he must register firstly in Hebron Municipality web-based system and have sufficient Bank Account balance from Alaraby Bank in order to get benefits from this service. The system does not provide the paying service only but also gives consumer the ability to report their comments and other essential e-Services.
no of pages 158, 18798, تكنولوجيا المعلومات 9/2006 , in the store
Keywords: E –payment